STRATEGI PEMANFAATAN INSTAGRAM SEBAGAI MEDIA DIGITAL MARKETING DALAM MENINGKATKAN OCCUPANCY HOTEL DIASA PANDEMI COVID-19 DI KABUPATEN BADUNG – BALI - Kadek Kreniawati; Ni Ketut Murdani; I Ketut Merta (Universitas Mahendradatta, 2022)
Bali has a tourism center in the Badung area, one of which isthe Paragon Resort Hotel. During the COVID-19 pandemic, many hotelsexperienced a decrease in visitors, therefore various promotional tips werecarried out by hotel management, one of which was using Instagram. This studyaims to determine how much influence Instagram as a digital marketing mediahas on increasing hotel occupancy during the COVID-19 pandemic in BadungBali Regency.In this study, there are two independent variables, namely DigitalMarketing (X1), Instagram (X2) and the dependent variable, namely IncreasingHotel Occupancy (Y). The research method used is quantitative research methodsand sample collection by convenience sampling method. Data was collectedthrough the distribution of online questionnaires via google form to 100respondents. The data processing technique was carried out by descriptiveanalysis through research instrument testing, classical assumption testing, andhypothesis testing. Through the multiple linear analysis test the results obtainedon the Instagram variable (X1) have an effect of 0.394 while the Digital marketingvariable (X2) has an influence of 0.576 on hotel occupancy (Y). In addition, fromthe results of the coefficient of determination test, there are results of .478, whichmeans that the influence of the independent variable (X) on the dependentvariable (Y) has a very large influence, namely 47.8%. The t-test results show thatthe significance value is <0.05, which is 0.010 in the X1 variable, while the X2variable also obtains a significance value of <0.05, which is 0.000 so that it canbe stated that Instagram and digital marketing media have a significant effect onincreasing hotel occupancy ( Y). In the F test there is a calculated F result that is44,452 and a significance of 0.000 < 0.05, this means that there is a simultaneouseffect of Instagram (x1) and digital marketing media (x2) on increasing hoteloccupancy (Y)